Control of electron beam current, charge, and energy spread using density downramp injection in laser wakefield accelerators - Céline S. Hue; Yang Wan; Eitan Y. Levine; Victor Malka (Matter and Radiation at Extremes, 2023)
Density downramp injection has been demonstrated to be an elegant and efficient approach for generating high-quality electron beams in laser wakefield accelerators. Recent studies have demonstrated the possibilities of generating electron beams with charges ranging from tens to hundreds of picocoulombs while maintaining good beam quality. However, the plasma and laser parameters in these studies have been limited to specific ranges or attention has been focused on separate physical processes such as beam loading, which affects the uniformity of the accelerating field and thus the energy spread of the trapped electrons, the repulsive force from the rear spike of the bubble, which reduces the transverse momentum p⊥ of the trapped electrons and results in small beam emittance, and the laser evolution when traveling in the plasma. In this work, we present a comprehensive numerical study of downramp injection in the laser wakefield, and we demonstrate that the current profile of the injected electron beam is directly correlated with the density transition parameters, which further affects the beam charge and energy evolution. By fine-tuning the plasma density parameters, electron beams with high charge (up to several hundreds of picocoulombs) and low energy spread (around 1% FWHM) can be obtained. All these results are supported by large-scale quasi-three-dimensional particle-in-cell simulations. We anticipate that the electron beams with tunable beam properties generated using this approach will be suitable for a wide range of applications.